The Occurrences of Harmful Algal Blooms (HABs) Species and Trophic Status Update in Kedung Ombo Reservoir - Rahman, Arif; Haeruddin; Prakoso, Kukuh (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Six harmful algal species were identified, with Aphanizomenon sp. being the most dominant, primarily from Cyanophyceae (blue-green algae). Kedung Ombo Reservoir is eutrophic, with low transparency, low dissolved oxygen (DO), and high phosphate levels (0.10–0.88 mg/L) contributing to HABs. Anthropogenic activities, including aquaculture, agriculture, and sewage, accelerate nutrient enrichment and phytoplankton overgrowth. Trophic State Index (TSI) confirmed eutrophic conditions, with HABs abundance linked to high phosphate concentrations. Urgent mitigation efforts like nutrient control, biomanipulation, and regular monitoring are needed to prevent further HABs outbreaks. Abstract Anthropogenic inputs affect the quality of freshwater ecosystems which causes ecological and health problems to aquatic ecosystems. Harmful algal blooms (HABs) associated with cyanotoxins often occur in nutrient-rich or eutrophic freshwater ecosystems. Kedung Ombo Reservoir in Indonesia has been previously classified as eutrophic to hypertrophic. Therefore, this study aimed to identify the occurrences of potential HABs species, measure the bio-physico-chemical water quality parameters, and update the trophic status of Kedung Ombo Reservoir. Sampling was done thrice during the dry season in 2022 from 5 stations. Twenty-two species of phytoplankton were observed in Kedung Ombo Reservoir. Anabaenopsis sp., Aphanizomenon sp., Ceratium sp., Mougeotia sp., Pandorina sp., and Ulothrix sp. were identified as potentially harmful species. Among those, the potentially HABs species, Aphanizomenon sp. was the most abundant (179,344 cells/L) and Cyanophyceae (205,539 cells/L) was the dominant group of phytoplankton. Kedung Ombo Reservoir had a water temperature of 29.49±0.41°C, phosphate of 0.27±0.25 mg/L, and alkaline pH of 7.90±0.39. Kedung Ombo Reservoir also had low transparency coupled with low dissolved oxygen concentration. The occurrences of HABs species were correlated with transparency and dissolved inorganic nutrients, especially phosphate concentrations. Kedung Ombo Reservoir showed eutrophic conditions based on Secchi depth, chlorophyll-a, total phosphorus, and TSI. Based on research findings, control and mitigation efforts are needed to overcome the eutrophication problems which disrupt the balance of the aquatic ecosystem in the Kedung Ombo Reservoir.